Increased Infectivity of Staphylococcus aureus in an Experimental Model of Snake Venom—Induced Tissue Damage - Saravia Otten, Patricia (2007)
Soft-tissue infection is commonly found in patients bitten by Latin American Bothrops snakes. Staphylococcus aureus, which is not present in the mouth of the snake, is frequently isolated from these infections. The effects of B. asper venom on infection with S. aureus were analyzed in a model of infection in envenomated mouse gastrocnemius muscle. Inoculation of 50 colony-forming units (cfu) of S. aureus was enough to cause infection in envenomated muscle, compared with >5x104 cfu without venom. This effect was also achieved by injection of venom myotoxin III (an A(2) phospholipase). A sarA mutant strain in which production of extracellular toxins and enzymes is up-regulated and binding of fibronectin, fibrinogen, and other host proteins is down-regulated was much less virulent than the corresponding parental strain, indicating that the ability of S. aureus to mask itself with host molecules might be more important than the effects of secreted toxins and enzymes in this kind of infection.